Determinants of Understanding Generation Z Financial Literacy in the Vocational School Students of Kahayan Hilir - alfina rahmatia; Siti Rahmah; Muslimah Muslimah; Aliya Khairunnisa (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to analyze the factors that influence financial literacy; gender, parents' income, parents' educational background, vocational school majors, and desire to continue the study. The data uses primary data with a quantitative method in which data is taken from questionnaires. The data analysis uses descriptive analysis from the data processing using Binary Logistic Regression with SPSS application software. The result reveals that gender has a significant influence on the understanding of Generation Z on financial literacy for students in Kahayan Hilir 1 Vocational School, while parents' income, parents' educational background, vocational school (SMK) majors, and desire to continue study do not have a significant influence to the understanding of Generation Z on financial literacy for students in Kahayan Hilir 1 Vocational School